Pengembangan Bahan Ajar (Buku) Teori Ekonomi Mikro Berbasis Media Pembelajaran Aplikasi Android - Putri Sari M.J. Silaban; Aurora Elise Putriku; Sabda D N Siahaan; Joko Suharianto (Cetta: Jurnal Ilmu Pendidikan, 2021)
In general, this study aims to improve the quality of learning in microeconomic theory courses in students of the Economic Education study program, Faculty of Economics, Unimed. In particular, this study aims to develop a feasible and effective Android-based macroeconomic theory learning media for learning. Based on the research results, the application of ed classes in the microeconomic theory course has been validated by 3 media and material experts. The results of expert validation resulted in a decision that the Ed Classes mobile learning application had a very high level of feasibility with a note that revisions needed to be made. After all revision notes were corrected, the mobile learning was then tested in small groups on 20 class C students in semester 3 of the Microeconomic Theory course. Based on the results of these trials, it is known that to test the effectiveness of the elasticity material it is concluded that the posttest learning outcomes of students after using mobile learning Ed Classes are significantly higher than the results of student pretest. Whereas in the practicality test it is known from three indicators, namely ease, usability and time effectiveness, all of which show satisfactory results at the strong level of practicality category. The results of this study are expected to increase learning motivation and also to increase student learning independence. It is hoped that the preparation of mobile learning can be as practical as it will make it easier for students to learn. Mobile learning applications, of course, can trigger students to master technology that makes human life easier and supports the industrial revolution 4.0 in the world of education.A maximum 200 - 250 words abstract in English with book antiqua font 11 point, 1 spacing, justify, italic. Abstract should be clear, descriptive, and should provide a brief overview of the problem studied. Abstract topics include discipline area, the purpose of article, reasons for the selection or the importance of research topics, research methods, hipothesis, the results of research, research’s contribution in discipline area, and a summary of the results. Abstract should end with a comment about the importance of the results or conclusions brief.